The Role of Artificial Intelligence in Advancing Public Services: Opportunities and Ethical Challenges - Amin, Fakhry; Simon, John Christianto; Nur, Muh.; Fauzih; Nurhamzah (International Journal of Science and Society, 2025)
The advancement of artificial intelligence (AI) has brought significant changes in various sectors, including public services. The implementation of AI in the government sector has the potential to increase efficiency, transparency, and speed of services to the public. However, the application of AI also raises various ethical challenges, such as personal data protection, potential algorithmic bias, and accountability in decision-making. This study aims to analyze the role of artificial intelligence in advancing public services and identify ethical opportunities and challenges that arise in the implementation process. The research method used is a qualitative approach, which involves reviewing various sources, such as previous research results, academic studies, and relevant policy documents. The collected data was analyzed systematically to identify key patterns and ethical implications related to the application of AI in the public sector. The results of the study show that AI has the potential to increase the efficiency of public services, but challenges related to privacy, transparency, and accountability are still major obstacles. The readiness of infrastructure and human resources are key factors in implementing AI in government bureaucracy. Therefore, strict regulations, cross-sector collaboration, and ongoing supervision are needed to ensure the ethical and equitable implementation of AI.